Relação entre posicionamento discursivo e estilo de gêneros do discurso: análise de reportagens publicadas em revistas voltadas aos públicos masculino e feminino - Drighetti, Bruno (2022)
Journalistic genres are often a source of studies in Discourse Analysis, not only for their great repercussion, but also for the fact that they play a fundamental role in the (re)construction of society's values and knowledge. There is, then, an urgent need to problematize the discourses that circulate in this field, as a way to understand it more deeply. Given this, this research arises with the proposal to analyze, based on discourse theories, the relation established between style and discursive positioning in productions of the discursive genre magazine reportage, considering, as presented Mussalim (2010), the existence of the style of a discursive formation. To ground the analyses, we anchored them in discourse theories, especially the theoretical-methodological postulate of Dominique Maingueneau (2011; 2015), which allows us to understand the genres of discourse as communication devices defined socially and historically. In addition, it was also necessary to resort to Bakhtin's theory (2011) to deepen the characterization and apprehension of discourse genres, as well as to think about the problem of style. Our corpus of analysis consists of five pairs of articles published in magazines with well-defined positions (especially regarding their market niche), GQ (aimed at the male audience) and Marie Claire (aimed at the female audience). When performing the analysis, as a way to minimize the interference of structural and thematic variations on style (DISCINI, 2012), the reportages were grouped in pairs from approximate thematic axes. As suggested by the results, there are indications that it would be possible to relate style and discursive positioning, the latter being linked, in the case of reportages, both to its niche market, as well as the editorial line of the vehicle. From this study, we hope to contribute to the studies of style from a discursive perspective and expand the discussions regarding the genres of the journalistic field, especially the reportage.